A national survey of the infrastructure and IT policies required to deliver computerised cognitive behavioural therapy in the English NHS. Issue 2 (1st February 2013) - Andrewes, Holly; Kenicer, David; McClay, Carrie-Anne; Williams, Christopher
Abstract : Objective: This study aimed to identify if patients have adequate access to Computerised Cognitive Behavioural Therapy (cCBT) programmes in all mental health trusts across England. Design: The primary researcher contacted a targeted sample of information technology (IT) leads in each mental health trust in England to complete the survey. Setting: Telephone, email and postal mail were used to contact an IT lead or nominated expert from each mental health trust. Participants: 48 of the 56 IT experts from each mental health trust in England responded. The experts who were chosen had sufficient knowledge of the infrastructure, technology, policies and regulations to answer all survey questions. Results: 77% of trusts provided computers for direct patient use, with computers in all except one trust meeting the specifications to access cCBT. However, 24% of trusts acknowledged that the number of computers provided was insufficient to provide a trust-wide service. 71% stated that the bandwidth available was adequate to provide access to cCBT sites, yet for many trusts, internet speed was identified as unpredictable and variable between locations. IT policies in only 56% of the trusts allowed National Health Service (NHS) staff to directly support patients as they complete cCBT courses via emails to the patients' personal email account. Only 37% allowed support via internet video calls, and only 9% allowed support via instant messaging services. Conclusions: Patient access to cCBT in English NHS mental health trusts is limited by the inadequate number of computers provided to patients, unpredictable bandwidth speed and inconsistent IT policies, which restrict patients from receiving the support needed to maximise the success of this therapy. English NHS mental health trusts need to alter IT policy and improve resources to reduce the waiting time for psychological resources required for patients seeking this evidence-based therapy.